Kehadiran Jamaah Tabligh di Malaysia dan Memoir Seorang Karkun Tabligh - Wong, Diana; Aziz, Arfan (Kontekstualita, 2014)
This paper explores the issue on the religious life of minority migrants in Malaysia. Through the research, it was found that the develompent of Tablighi Jemaat in Malaysia which was identified as âIndian Jemaatâ, grow into an Islamic missionary movement, aiming for the Malays and others, using solicitation and persuasive inducement (tasykil) and among them are: academics, bureaucrats and the Malaysian clerics. Tasykil has been done since the 1950s. The three objects of Tablighi Jamaat missionary in Malaysia that became the foundation of its development up to now. Through memoir a member of Tablighi Jamaat (karkun), it was also found that the sermons have become migrant religious activities, not only for the Malaysian migrants outside the country, but also among migrants from neighboring countries who are studying and working, even among Rohignya refugees in Malaysia. Keywords: kehidupan keagamaan, Jamaah Tabligh, Malaysia, memoir Hanapi.